DI-001 Ciclosporin-associated thrombotic microangiopathy. (24th February 2014) - Alarcon-Payer, C; Jurado Chacon, M; Caparros Romero, S; Romero Aguilar, A; Calleja Hernandez, MA
Abstract : Background: The development of thrombotic microangiopathy (TPP) is well documented in organ transplant recipients, in most cases associated with calcineurin inhibitors. The mechanism by which TPP arises is from inhibition of the enzyme ADAMTS13. Purpose: To analyse those cases of TPP associated with ciclosporin in patients undergoing bone marrow transplantation (BMT) in a tertiary hospital. Materials and methods: Retrospective observational study that reviewed the medical records of patients who suffered TPP associated with BMT from 2008 to 2013. Results: In the period of study, of the 45 patients undergoing BMT and treated with ciclosporin, 7 suffered ciclosporin-associated TTP. In 2 patients TPP emerged when ciclosporin was added to sirolimus and in 5 when sirolimus was added to ciclosporin. The reason for the addition of these immunosuppressants was acute graft versus host disease (GVHD) in 2 patients and in 5 chronic GVHD. TTP was handled by suspending ciclosporin and maintaining sirolimus and corticosteroids in 3 patients whereas in 4 both ciclosporin and sirolimus were suspended. In 4 patients phenytoin was added, in 2 haemodialysis was performed, in 3 plasmapheresis was done and in 1 rituximab was administered. The use of rituximab generates good results because it decreases the antibodies responsible for inhibiting the ADAMTS13 enzyme. In all the cases the duration of basal active levels of ciclosporin after it had been suspended was about four months. Ciclosporin is a substrate of P-glycoprotein (P-gp) and it is thought that ABCB1 SNPs might influence ciclosporin intracellular concentration and modulate its immunosuppressant activity. Conclusions: The appearance of TPP associated with ciclosporin in patients undergoing BMT is a concern. All cases present a clinical condition characterised by moderate to severe haemolytic anaemia, negative direct Coombs, thrombocytopenia, elevated LDH and creatinine, presence of schistocytes >4% and kidney disorders. The reason why this phenomenon occurs is unknown, but it seems to be an ABCB1 genetic polymorphism affecting the intracellular concentrations of ciclosporin. No conflict of interest.